Complete distal deltoid muscle detachment: a case report - Madi, Naji S.; Issa, Rayane; Koaik, Youssef; Al-Taki, Muhyeddine (Sportverletzung · Sportschaden, 2020)
Background The deltoid is a large triangular muscle at the shoulder. It attaches proximally to the clavicle, acromion and scapula, while distally it attaches to the lateral deltoid tuberosity. Ruptures are rare, and the literature only reports cases of proximal detachment. In this article, we report the first case of distal traumatic deltoid muscle detachment and its successful management.Case A young female sustained a traumatic injury following a Jet Ski accident with loss of consciousness. A complete distal rupture of the deltoid muscle was diagnosed after the basic functions were regained and a thorough musculoskeletal examination could be conducted. A conservative approach helped her to regain an acceptable shoulder function, but there was persistent pain upon activity and cosmetic scarring. The patient underwent surgical reconstruction. Postoperatively, she recovered satisfactorily.Discussion Distal detachment of the deltoid muscle is rare. The choice for surgical treatment may be undertaken based on several factors including functional status and patient-based assessment.
Keywords: deltoid; distal fixation; rupture; complete; shoulder; trauma; jet ski